A REVIEW OF HALAL GOVERNANCE IN MALAYSIA FROM THE PERSPECTIVES OF MAQASID AL-SHARIAH - Che Mohd Zain, Che Rosmawati; Zakaria, Zalina (Journal of Shariah Law Research, 2022)
As an Islamic subject, halal promulgates halal administration with the Islamic principles as the foundation for the halal governance sphere. For several years, many issues of halal-related matters have occurred in Malaysia, such as false halal DNA, false halal certification, and irresponsible business people who do not care about halal sensitivity when producing their products and services. All those halal issues exist because the parties who deal with anything under the so-called halal umbrella lack understanding of Islamic law’s teachings, principles, and guidelines in executing certain matters diligently and faithfully. Islam has provided a perfect dominion and direction for halal, which is the Islamic law governing halal-related matters towards success. This article reviews the essence of Islamic law objectives, known as maqasid al-Shariah, namely perseverance of religion, perseverance of physical self, perseverance of knowledge, perseverance of family, and perseverance of wealth by analysing those objectives as principles in regulating the sustainability of halal governance in Malaysia. The research method is a systematic review of literature from journal articles, books and other related materials. Undeniably, those principles of maqasid al-Shariah are essential in developing good halal governance for a better future for halal-related matters sustainability in Malaysia. Such a breakthrough in halal governance will indicate halal stakeholders in building the country as a leader of the halal hub in the global halal ecosystem.